Adherence to tuberculosis preventive therapy measured by urine metabolite testing among people with HIV. (1st January 2020) - Kendall, Emily A.; Durovni, Betina; Martinson, Neil A.; Cavalacante, Solange; Masonoke, Katlego; Saraceni, Valeria; Lebina, Limakatso; Efron, Anne; Cohn, Silvia; Chon, Sandy; Chaisson, Richard E.; Dowdy, David W.; et al.
Abstract : Objectives: Tuberculosis preventive therapy for people living with HIV is effective, widely recommended, and increasingly prescribed, but completion rates are less than ideal, and adherence is not typically monitored. We sought to quantify adherence to isoniazid preventive therapy using a urine metabolite assay. Design: Two cross-sectional surveys. Setting: Rio de Janeiro, Brazil, 2008–2009; and Northwest Province, South Africa, 2018–2019. Participants: Two hundred and three Brazilian and 93 South African patients attending HIV clinics with active prescriptions for isoniazid preventive therapy Main outcome measures: Self-reported isoniazid adherence, paired with semiquantitative measurement of urine isoniazid metabolites. Results: By self-report, 90% of patients [95% confidence interval (CI) 86–93%] reported having taken a dose of isoniazid on the day of enrollment or the preceding day, and 91% (95% CI 87–94%) reported missing an average of one dose or fewer per week. By urine testing, only 65% (95% CI 59–70%) of all patients, and 69% (95% CI 63–74%) of those who reported having taken isoniazid on the current or preceding day, had detectable urine metabolites (expected in 95% of patients at 24 h). Longer time since starting preventive therapy was independently associated with a negative urine test for isoniazid metabolites (adjusted prevalence ratio 1.11 per month of isoniazid, 95% CI 1.05–1.18). Conclusion: Adherence to isoniazid preventive therapy among patients with HIV in Brazil and South Africa is inadequate, is overestimated by self-report, and declines with time on treatment. Shorter regimens for TB preventive therapy may improve adherence and completion, but adherence support for all patients may be necessary.